Nucleic acid testing for tuberculosis at the point-of-care in high-burden countries - Niemz, Angelika (2012)
Early diagnosis of tuberculosis (TB) facilitates appropriate treatment initiation and can limit the spread of this highly contagious disease. However, commonly used TB diagnostic methods are slow, often insensitive, cumbersome and inaccessible to most patients in TB endemic countries that lack necessary resources. This review discusses nucleic acid amplification technologies, which are being developed for rapid near patient TB diagnosis, that are in the market or undergoing clinical evaluation. They are based on PCR or isothermal methods and are implemented as manual assays or partially/fully integrated instrument systems, with associated tradeoffs between clinical performance, cost, robustness, quality assurance and usability in remote settings by minimally trained personnel. Unmet needs prevail for the identification of drug-resistant TB and for TB diagnosis in HIV-positive and pediatric patients.